Paut Neteru: Dreams of Leadership and Liberation—An Autoethnography of a Black Female Charter School Leader Using An Africentric Approach - Williams, Patricia Linn (Frontiers in Education, 2021)
This article seeks to document and critique concepts of social and material inequalities embedded in institutional policies and practices in neoliberal education, utilizing autoethnography to explore the obstacles and experiences of a Black female charter school leader using an Africentric approach to educating Black children. A conceptual framework that blends African-centered pedagogy, African womanism, and transformational leadership was used to guide the qualitative autoethnographic study that anchors this article. Use of the autoethnographic method provides an opportunity to examine the relational dynamics of the experiences of this Black female charter school leader in the cultural context of the Black community and neoliberal education. Data analysis was captured from autobiographical storytelling within three key time periods or epochs of the researcher’s 17-year experience starting, operating, and closing a charter school. The article highlights findings that indicate how attempts to implement an African-centered approach to educating Black children, in a DC charter school, in the U.S. Eurocentric education model, in the neoliberal era, was compromised by neoliberal policies; and illustrates how reported findings support the need to continue to examine how children of color can be educated, not just schooled, in a manner that places them at the center of their learning, builds agency, and develops them into creative and critical thinkers and future builders.